International Relations and Contemporary Artwork: Canadian Settler Colonialism, Indigenous Self-Determination, and Decolonizing Visuality - Merson, Emily Hannah (2015)
In this project I analyze the international dimensions of sovereignty, political self-determination, and creative self-expression by Indigenous contemporary artists in the context of Canadian settler colonialism. My key research question is: how does the conventional International Relations (IR) imagination of state formation and world ordering through territorial sovereignty displace the violences of Canadian settler colonialism? With a transnational feminist analysis I examine visual expressions of the Canadian settler colonial imaginary of world ordering by territorial sovereignty expressed at particular historical moments and how the work of Indigenous artists, curators, academics, and communities calls attention to the power relationships and violences of these international processes. Methodologically, I analyze how visual methods of knowledge production in art museums, galleries, and international art exhibitions express and inform conventional identities, policies, institutional practices, divisions of labour, academic theories, and popular ideas about Canadian nationalism, subjectivity, and settler colonial claims to territorial sovereignty. I demonstrate how contemporary visual artwork by Brian Jungen, a Dane-zaa First Nations artist of European descent, and Anishinaabe artist Rebecca Belmore unsettle the conventional Westphalian imaginary of sovereignty in IR and offer transformative potentials for decolonizing material conditions of power, agency, and visuality in international politics. I analyze how Jungen and Belmore’s artwork and framing of their projects in the contexts of the international political conditions within which they live and work intervenes in mainstream Canadian and global visual cultures in terms of political struggles over colonial ethnographic institutional visual methods, Indigenous peoples’ experiences of dispossession, colonial commodification, sexual violence, and Indigenous peoples’ lands and waterways reclamations. Taking the lead from the artists’ self-identified entry ...